Fluctuation Relations and Nonequilibrium Thermodynamics in Classical and Quantum Systems - De Chiara, Gabriele (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue contains novel results in the area of out-of-equilibrium classical and quantum thermodynamics. Contributions are from different areas of physics, including statistical mechanics, quantum information and many-body systems.